The Portrayal Of Jesse Owens’ Character As The Representation Of Male African-American Athlete In Stephen Hopkins’ Race (2016): New Historicism - Zakiyah Dania Billah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
In the 1930s, African-American male athletes faced segregation and discrimination due to their skin color. Modern biographical films now offer a more accurate representation of their struggles and achievements. This research examines how the movie “Race” (2016) portrays Jesse Owens, a male African-American athlete from the 1930s, and its implications for present-day US race relations. Through qualitative analysis using Narrative and Non-Narrative methods, we apply Stephen Greenblatt’s New Historicism to explore the movie's depiction of Owens. By comparing the film to historical records, we find that "Race" neglects to show Owens’ dedication to sports, education, work, and the significant influence of his Irish first coach. These omissions are connected to the continued exclusion of African-Americans in contemporary American society. This study reaffirms the persistence of white supremacy beliefs and stereotypes surrounding African-American athletes, portraying them as solely focused on sports. The portrayal of Jesse Owens in the movie mirrors the current experiences of African-American male athletes, who still grapple with stereotypes and racial discrimination, even in the aftermath of President Obama’s tenure.